EXAMINING FLOW STATES AND MOTIVATIONAL PERSPECTIVES OF ASHTANGA YOGA PRACTITIONERS - Leslie Lynn Phillips (University of Kentucky, 2005)
Flow state refers to an optimal psychological experience and is associated with a number of experiential qualities one of which is complete absorption in the task at hand. Self-determination theory provides a framework for examining the relation between different types of motivation and flow because it distinguishes among different forms of motivation based on the degree that they can be considered self-determined. Although flow has been studied among athletes and, to a lesser degree, exercisers, no studies ave focused on the flow experiences of yoga practitioners. Yoga, which originated in India, has been gaining popularity in the United States. The purpose of this descriptive study was to examine the flow experiences and motivational perspectives of ashtanga yoga practitioners. Five specific aims were addressed. A sample of 127 ashtanga yoga practitioners were recruited from six yoga studios in various locations across the United States. Participants completed a series of questionnaires related to flow experiences, motivational orientation, yoga practice characteristics, and sociodemographic information. The majority of the participants of the study were women, highly educated, and approximately 40 years old. The participants demonstrated a strong commitment to yoga practicing on average 4 times per week for over 1.5 hours. The majority had more than 2.5 years of ashtanga yoga experience. They reported strong intrinsic and selfdetermined extrinsic motivation to practice ashtanga yoga. They reported experiencing flow during ashtanga yoga practice and at least moderately endorsed all nine dimensions of flow state. Higher scores on the EMS subscales of intrinsic motivation (IM) to accomplish things and IM to experience sensation were predictive of higher flow state for the practitioners. The respondents' yoga flow scores were significantly higher than the flow scores associated with a comparison "other" physical activity participated in currently or in the past. Finally, age (inversely) and years of ashtanga yoga experience were predictive of flow experiences for this group of yoga practitioners. For those interested in the study of motivation, these findings contribute to the understanding of the relation between flow and motivation and how "enjoyment" may be manifested within the context of physical activity.